(untitled) (Linguostylistic Studies, 2020)
Nicknames which come into being as an addition to the person’s basic name are unofficial anthroponyms with the help of which the environment individualizes or characterizes a person. Marking people with nicknames is a characteristic feature of the football area in the whole world In Ukrainian linguistics, the unofficial personal names of the football players have not been the object of study yet, therefore their analysis is topical. The aim of the article is to analyze unofficial persons’ names of football players who played in the Ukrainian teams in 20-30ies of the ХХth century. The task of the study is to trace tendencies in the unofficial naming of people and to draw the social-linguistic conclusions about using anthroponyms in the sports area. The basic method of the research is a discursive analysis of the facts taken from printed resources (first of all, from the Ukrainian sports media of that time and archives) and a well-grounded description of the findings. The biggest group of football players’ nicknames are those which are diminutive forms of players’ names. Among the nicknames that came into being as a result of using diminutive affectionate forms of names, there are such which have been created according to the Ukrainian pattern and also according to the pattern of Polish (in Halychyna), Czech and Hungarian (in Zakarpatia), and Russian (in Volyn region) diminutive form formation tendencies. It is the proof of different foreign influences on the emergence of Ukrainian football players’ nicknames since the footballers played for the teams of different parts of Ukraine, belonging to different countries at the time). One of the most popular models of creating nicknames was one that followed the pattern of transforming surnames, most frequently by way of cutting (taking parts of surnames). A series of nicknames were created with a focus on the characteristic features of football players’ appearance or their characters; motivation for creating nicknames was combination of both external and internal characteristics of football players. Most often nicknames were the result of using metaphor and synecdoche as variations of lexical-semantic way of creation. Analysis of Ukrainian football players’ nicknames in 20-30ies showed that the motivational basis for those anthroponyms were diminutive forms of players’ names, their surnames, names of different objects, features, and ways of creating those names are metaphor, synecdoche and parts of surnames. Further research is suggested to trace dynamics of creating football players’ nicknames in various periods of the Ukrainian football development.